The effect of accrual earnings management and real earnings management on earnings persistence and cost of equity - Zumratul Meini; Sylvia Veronica Siregar (Journal of Economics, Business, and Accountancy Ventura, 2014)
There are two kinds of earnings management: accrual earnings management and real earnings management. This study aims to assess the effect of earnings management on earnings persistence and cost of equity on 155 firms listed on the Indonesia Stock Exchange during the 2001-2010 periods. Analysis in this study uses the Panel Regression Fixed Effect method. The result shows that accrual and real earnings management do not weaken earnings persistence. Furthermore, it was found that accrual earnings management has a positive effect on the cost of equity. Conversely, earnings management through real activity manipulation has a negative effect on the cost of equity. These results may indicate that investors are already aware of a firm’s earnings management behaviors through discretionary accrual, but may still not be aware of the negative impact of earnings management through real activity manipulation.